A human-specific VNTR in the TRIB3 promoter causes gene expression variation between individuals - Örd, Tiit; Puurand, Tarmo; Örd, Daima; Annilo, Tarmo; Möls, Märt; Remm, Maido; Örd, Tõnis (PLoS genetics, 2020)
Tribbles homolog 3 (TRIB3) is pseudokinase involved in intracellular regulatory processes and has been implicated in several diseases. In this article, we report that human TRIB3 promoter contains a 33-bp variable number tandem repeat (VNTR) and characterize the heterogeneity and function of this genetic element. Analysis of human populations around the world uncovered the existence of alleles ranging from 1 to 5 copies of the repeat, with 2-, 3- and 5-copy alleles being the most common but displaying considerable geographical differences in frequency. The repeated sequence overlaps a C/EBP-ATF transcriptional regulatory element and is highly conserved, but not repeated, in various mammalian species, including great apes. The repeat is however evident in Neanderthal and Denisovan genomes. Reporter plasmid experiments in human cell culture reveal that an increased copy number of the TRIB3 promoter 33-bp repeat results in increased transcriptional activity. In line with this, analysis of whole genome sequencing and RNA-Seq data from human cohorts demonstrates that the copy number of TRIB3 promoter 33-bp repeats is positively correlated with TRIB3 mRNA expression level in many tissues throughout the body. Moreover, the copy number of the TRIB3 33-bp repeat appears to be linked to known TRIB3 eQTL SNPs as well as TRIB3 SNPs reported in genetic association studies. Taken together, the results indicate that the promoter 33-bp VNTR constitutes a causal variant for TRIB3 expression variation between individuals and could underlie the results of SNP-based genetic studies.